Balancing water scarcity and quality for sustainable irrigated agriculture. Issue 5 (8th May 2015) - Assouline, Shmuel; Russo, David; Silber, Avner; Or, Dani
Abstract The challenge of meeting the projected doubling of global demand for food by 2050 is monumental. It is further exacerbated by the limited prospects for land expansion and rapidly dwindling water resources. A promising strategy for increasing crop yields per unit land requires the expansion of irrigated agriculture and the harnessing of water sources previously considered "marginal" (saline, treated effluent, and desalinated water). Such an expansion, however, must carefully consider potential long‐term risks on soil hydroecological functioning. The study provides critical analyses of use of marginal water and management approaches to map out potential risks. Long‐term application of treated effluent (TE) for irrigation has shown adverse impacts on soil transport properties, and introduces certain health risks due to the persistent exposure of soil biota to anthropogenic compounds (e.g., promoting antibiotic resistance). The availability of desalinated water (DS) for irrigation expands management options and improves yields while reducing irrigation amounts and salt loading into the soil. Quantitative models are used to delineate trends associated with long‐term use of TE and DS considering agricultural, hydrological, and environmental aspects. The primary challenges to the sustainability of agroecosystems lies with the hazards of saline and sodic conditions, and the unintended consequences on soil hydroecological functioning. Multidisciplinary approaches that combine new scientific knowhow with legislative, economic, and societal tools are required to ensure safe and sustainable use of water resources of different qualities. The new scientific knowhow should provide quantitative models for integrating key biophysical processes with ecological interactions at appropriate spatial and temporal scales.